Düşünce Ve Duyular Ekseninde Mimarlık Bilgileri - Altunkozaoğlu, Altay (Fen Bilimleri Enstitüsü, 2012)
Mimarlık; çevresel etkenler,toplumsal unsurlar, kültürel birikim, düşünsel ürünler ve bilimsel bilgi gibi birçok bileşenin farklı oranlardaki katkı ve şekillendirmeleri doğrultusunda somut ürünler ve düşünsel yaklaşımlar ortaya koyan çok girdili bir disiplindir.Dolayısıyla mimarlık üzerine fikir yürütülürken sadece mimarlığa dair teori ya da uygulama temelli bir tartışma konusu tayin edebilmek ve bu konu üzerinden düşünsel sonuçlara ulaşmak mümkün değildir.Bu noktada insan bilinci ile mimarlık ürünü arasındaki ilişkiyi şekillendiren unsurlar olarak duyular, zamanın değişenlerinden bağımsız bir araştırma konusu olarak belirmektedirler. Duyusal bilginin oluşturulma ve ele alınış yöntemleri, bu yaklaşımların arkalarındaki düşünceler, farklı zamanların farklı mimarlıkları üzerinden mimarlığın değişen ve değişmeyen bileşenlerinin farkedilebilmesini sağlayan önemli bir çalışma konusudur. Çalışma dahilinde iki önemli bilimsel eşik noktası ve bu iki eşik noktası arasındaki süreç, duyusal mimarlık bilgisine dair oluşturulan farklı bilgi ve yaklaşımlar üzerinden irdelenecektir. Aydınlanma devrinde yeniden şekillenen bilgisel sınıflandırmalar ve sanayileşmenin sağladığı teknik olanaklar doğrultusunda oluşan modern mimarlık hareketi, belirtilen değişikliklerin toplumların yaşantıları üzerindeki güçlü etkilerine dair yeni ve akılcı çözümler sunma iddiasında olmuştur. Bu hareketin çıkış noktası olan akılcılık ilkesiyle bir çelişki teşkil edecek şekilde kuramsallaştırılan duyu bilgileri ise mimarlığın ikili bilgi yapısını ve kişisel irade boyutunu gözler önüne sermektedir. 2.Dünya Savaşı’nın ardından büyüyen kentleşme ve yeniden yapılanma sorunları; yönetim odaklarının, bilimsel ve ampirik fiziksel çevre çalışmalarını kişiselleştirilmiş mimarlık bilgilerine tercih etmesiyle çözümlenmeye çalışılmıştır.Kentsel yaşama koşullarında iyileştirme ve sıfırdan inşa edilen çevrelerin tarafsız bilgilerle oluşturma çabaları, 20. Yüzyıl kentlerinin çehrelerini şekillendiren en büyük unsur olmuştur. Bu devir,kamu yapılarındaki cephe açıklıklarını tayin eden gerekli ışık değerlerinden, yolların güzergah ve yoğunluklarını etkileyecek işitsel komfor bilgilerine kadar pek çok noktada farklı mimarlık bilgilerinin üretilmesine sahne olmuştur. Bu bilginin üretilme şeklindeki akılcı tavır modern mimarlığın araçsalcılığından farklıdır ve kendi çelişkilerini barındırır. Laboratuarların sınırlarını reddeden bilim insanları, insanların düşünce, plan ve duygularını dışlayan duyusal komfor arayışlarıyla bir anlamda laboratuarları kentlere taşımışlardır. Kuantum anlayışının baskın bilimsel görüş olarak kabul görmesiyle birlikte davranış ve fiziksel çevre üzerinden ilerleyen duyusal bilgi çalışmaları daha öğesel, bütüncül ve çok disiplinli bir çalışma alanına dönüşmüştür. İnsanın bütüncül duyu örgüsünün ayırdındaki bilimsel bilgi, çok duyulu etkileşimleri gündelik hayata taşımakta ve mimarlığı, görsel etkiyi aşan, bütün duyusal verileri önemseyen çok disiplinli bir üretim eylemi olmaya doğru götürmektedir.

Architecture is a multiple inputted discipline that creates solid objects and ideologic approaches, meanwhile being directly effected from various crucial elements such as the cultural heritage, social contents, philosophical ideas and the scientific knowledge. This multiple informationary causes and effetcs prevent architecture from being a certain subject to be discussed in an isolated manor with concrete results. At that point, the senses which build the perceptional bridge between the human consciousness and the architectural product becomes an invariable that is to be an objective field of study for the architecture. The derivation of the sensory information, the way architects aproach to it and the ideas behind these actions help revealing the variable and the invariables of the architecture through different times. The study includes two sequential paradigmic shifts in scientific knowledge and the period between those shifts. Those three differing periods will be considered through different architectural sensory informations and approaches. First period starts with the seperation of the natural Sciences and philosophy. This major informational change revealed itself in architecture by the end of the 19th century. Modernist architecture was born out of two major things. The enlightenment that revolutionized and reshaped the structure of the knowledge and the industralization of the production force. Modernist architecture proposed new solutions to the masses that were massively effected from the rapidly changing artificial environments that were created out of mass productions. Those solutions were based on rationalization. But the major conflict created out of this rationalization principle can be observed through the instrumentalized sensory informations created by the modernist architects which are heavily customized yet manifested to be universal. This reveals the duality of the architectural knowledge. One of the most significant examples of this attempt was Le Corbusier s life long works and writings. The architect tried to catalogue all the assumed definitions and dimensions needed for the daily architectural practice in a theorotical manor in his compilation books named Le Modulor. The ideas documented on those writings were partly realized through most of Le Corbusier s works. The dualistic and blurry properties of architectural knowledge that do not change over time are revealed as a conflict throughought the works of Le Corbusier and most significantly on his religious buildings. The idea of a religious building includes the symbolism of the religion and the traditions it holds within it s very programme. The modernist approach Le Corbusier advocated cherished the symbolism of the natural material, the plan and the shapes that were created throughout the particular projects rather than a constant symbolism. The instrumentalized sensory informations derived for the building of La Tourette shows the conflict created out of the modernist approach significantly. La Modular principles applied to the meditation chambers of the monastery seem to work well yet the same proportions applied to more daily functioning spaces crated rather questionable results in other buildings of the architect. Thus the outer facades of La Tourette were not created for any apparent functional reason. Those facades that were based on a geometrical system which was derived out of Xenakis s musical composition Metastasis. Seemingly architects favored the mathematical order through both vision and hearing sensories. While this approach can be explained through an arithmetical logic, it cannot be explained with any logical reason as the modernist architecture manifested. The subjectively idealized arithmetic instruments were used for creating different sensory results. This approach can be traced back to the enlightenment era. The idea of Musica Universalis which was dominant throuought Pythagoreans in ancient Greece was revived in the 17th century. This ideology foretold that the roots of all nature were derived out of Mathemeatics. Mathematics can explain the mechanisms of any natural phenomenon regardless of the sensory results. This large order of natural explanation can be seen through La Tourette despite the subjective modifications of the architect .The rationalizating of one of the most important modernist architectural method thus reveals it self to be subjective and idealized. Second period starts with the early 20th century s mass building programmes and the behaviorist environment approach. The problems of reconstruction and the urbanization of the man-made environments were evermore increased by the end of the Second World War. The governing forces preferred the emprical scientific knowledge derived out of physical environment to the customized architectural manifests. The work of (re)constructing the urban environment with the help of the emprical knowledge was the major force that shaped the faces of today’s urban environments and also the improvements of the poorly conditioned industrial cities of the Europe and the Americas. From the light examinings that led to the definitions of the opacity proportions on the outer surfaces of the public buildings, to the noise control experiments that helped the shaping of the roads and their densities, this period of time is full of emprical sensory information created by the physical environment scientists. The rationalization behind this act was far different and more objective than the modernist movement yet it had it’s own conflicts. The Scientists that refused the boundaries of the laboratories, seemed to be carrying the idea of the laboratory to the urban environment with the denial of the human realities such as imagination, emotion, plans and intentions in defining the sensory comforts of a building. The behavorist psychological approach of the era tried to create other architectural catalogues regarding the experiments carried out testing the sensory capabilities of the people. The famous Hawthorne Experiments which were carried out after the big deppression in search for greater profits first started the improvements of the physical environments through psychological knowledge. The examining of the physical environment through scientific knowledge and methods started to define the minimum sensory conditions of the industrial environments effecting the governing policies of the mass rebuilding programmes. But the design knowledge that was to be created by the scientists seemed to be even more ineffective than the scientific knowledge tried to be created by the architects in the early 20th century. The solidified and inorganic artifical environments, from this age on became a majour focus for both the opposing psychologists and philosophers which helped the architectural theory mature and free from the individual building manifests and extremely rational behaviorist experiments. The third period includes the quantum thus the cognitive revolution. With the arising quantum physics, the psychological approach that depended on behavior was ultimately replaced by the cognitive sciences that worked in a multidisciplinary way. The human consciousness is now regarded to be an objective scientific study field. This important paradigmic shift in psychology led to the understanding of the multisensory nature of the human perception. The uniqueness of a spatial experiment can now be explained through the unitary perceptional mechanisms of the human mind scientificaly. This revolutionary new understanding of the human perception helps the questioning of the purely empirical methods of the behaviorist approaches towards the artificial environments. Today’s cognitive scientists think of the multi-sensory interactions and environments as a crucial instrument for the treatment of the mentally and perceptionally challenged people. The technology created for these special environments are also applied to the daily artifical environments of ordinary urban people. Another rather theorotical approval for the multi-sensory perceptions of the human nature can be seen through Peter Zumthor’s buildings. Zumthor buildings tend to favor the unique spatial experience over the construction methods and the programmes. This approach gives his buildings almost synesthetic qualities in perceptional terms. While Zumthor buildings are not directly inspired by the cognitive revolutions of the recent scientific discoveries, they cherish the importance of the whole perceptional mechanisms of the human nature in search for unique spatial experiences. The existence of the mentioned recent archtectural approaches show us that the architecture of the tomorrow will blend the individual preferences with the universal scientific knowledge in unique occurences. This search of architecture will not be properly mentioned in terms of visual aesthetics since it will be in touch with all human senses.
Architectural Knowledges Through The Ideas And Senses
Tez (Yüksek Lisans) -- İstanbul Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 2012
Thesis (M.Sc.) -- İstanbul Technical University, Institute of Science and Technology, 2012
Keywords: Duyu; Araçsal duyu bilgisi; Modern manifesto; Sinestezi; Bilişsel Devrim; Fiziksel Çevre Kontrolü; Davranışçı psikoloji; Senses; Instrumentalized perceptional knowledge; Modern maniphestos; Synesthesia; Cognitive revolution; Physical environment studies; Behavioral psychology